PENGEMBANGAN BUKU DIGITAL UNTUK MEDIA MENINGKATKAN MOTIVASI BELAJAR - Rahmawati Eka Saputri; Aisha Nur Saleha; Nur Rizki Aulia; Saidah Nur Permata (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This article reports on the development of digital books as a medium to increase learning motivation of grade IV students. This research aims to develop digital books as innovative learning media to increase students' learning motivation. The background of this research is the low interest of students in learning caused by the use of conventional learning media that is less interesting. The subjects of the limited trial were elementary school students at the middle grade level. Data were collected through observation, questionnaire on learning motivation, and interview. The results showed that the digital book developed was feasible to use based on the assessment of material experts, media experts, and positive responses from students. In addition, there was an increase in learning motivation after students used the digital book in the learning process. Thus, the digital media book developed proved to be effective as an alternative learning media that can increase student learning motivation.